EXPECTED SCENARIOS OF RECOVERY FROM THE CRISIS OF ECONOMY OF RUSSIA - V. Makhalin (Publishing House of the State University of Management, 2016)
Some expected scenarios of recovery from the crisis of economy of Russia offered by famous economists, scientists, authorities and the governments are considered. Conclusions are formulated.